Entrepreneurial efforts and opportunity costs: evidence from twitch streamers - Philip Wollborn; David Dornekott; Ulrike Holder (International Entrepreneurship and Management Journal, 2023)
With the rise of digital platforms, individuals' possibilities to generate income have increased drastically. In this context, we present digital content creation as a form of (digital) entrepreneurship that is characterized by potentially high but also uncertain revenues. As the cost structure of content creation mostly depends on opportunity costs, it stands in contrast to other popular platform-work options. We demonstrate how a stark and unexpected reduction in opportunity costs affects the actual decision to produce digital content. Exploiting the first wave of the COVID-19 pandemic, we measure how individuals (streamers) who operate on a live streaming platform, respond to a sudden change in external factors while accounting for individual differences in initial conditions. We observe intensified efforts across the spectrum of streamers and find particularly strong reactions from newcomer streamers. We further show that only the most successful newcomers sustain their increased efforts even when opportunity costs start to rise again. Our results are consistent with the initial assumption that an individual's decision on taking up or intensifying entrepreneurial efforts on digital platforms is strongly affected by their opportunity costs. The results further imply that there is a large potential in individuals who might be willing to become entrepreneurs but are restricted by external conditions. As platform-based digital entrepreneurship offers high flexibility and very low entry barriers, measures for lowering opportunity costs could therefore help to unleash this potential. To maintain a steady influx of new talents, content platforms should increase their support for smaller creators and policymakers should provide easily accessible platforms to ease the way into entrepreneurship for these individuals.
Keywords: 650; Digital entrepreneurship; Content creation; Self-employment; Opportunity costs; Platform work; Live streaming; COVID-19; Difference-in-differences